Editorial - Mejia Chiang, César (2018)
The global reach of certain events provides Communication Sciences researchers the unparalleled opportunity to think about the ethical role in generating, disseminating and feedback messages, in both traditional Media and social networks. Euphoria and enthusiasm are elements that surround this type of events and it is communicator responsibility to offer rigorous content that provides data and useful information to the audience, beyond “colorful”, superficial and easily forgettable reports. Being exhaustive and responsible does not necessarily mean being “boring” or turning away from the emotionality experienced in social context. Working with news components, communicator has the task of being consistent with their professional values, developing messages that contribute to the productive debate of issues, without exploiting prejudiced or stereotyped aspects, which only entangle and hinder dialogue.